The importance of the presence of foreign capital in the context of ensuring the stability of the banking system - Chen Jie (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
Object of research is the Chinese banking system, focusing on the integration of foreign capital and its impact on banking stability. Subject of research modern approaches and methods for assessing the role of foreign capital in ensuring the stability of China's banking system, using macroeconomic and prudential indicators. Purpose of qualification master's work is to examine the influence of foreign capital on banking stability in China, systematize theoretical and empirical approaches to financial resilience, and develop recommendations for optimizing macroprudential tools and regulatory frameworks to align with international standards. The study synthesizes theoretical insights and practical analyses, offering recommendations for enhancing the stability of China's banking system. The findings highlight foreign capital’s role in technological advancements, risk management, and market efficiency, while addressing challenges such as regulatory compliance and systemic risks.
Важливість присутності іноземного капіталу в контексті забезпечення стабільності банківської системи
Scientific advisor: Kochorba Valeriia, PhD of economics, associate professor, department banking business and financial technologies
Keywords: SOCIAL SCIENCES::Business and economics::Economics; foreign capital; banking stability; financial resilience; emerging economies; risk management; Basel III; foreign direct investment; regulatory frameworks; financial inclusion; digital banking